Rapid intravenous rehydration of children with acute gastroenteritis and dehydration: a systematic review and meta-analysis - M. A. Iro; T. Sell; N. Brown; K. Maitland (BMC, 2018)
Abstract Background The World Health Organization (WHO) recommends rapid intravenous rehydration, using fluid volumes of 70-100mls/kg over 3-6 h, with some of the initial volume given rapidly as initial fluid boluses to treat hypovolaemic shock for children with acute gastroenteritis (AGE) and severe dehydration. The evidence supporting the safety and efficacy of rapid versus slower rehydration remains uncertain. Methods We conducted a systematic review of randomised controlled trials (RCTs) on 11th of May 2017 comparing different rates of intravenous fluid therapy in children with AGE and moderate or severe dehydration, using standard search terms. Two authors independently assessed trial quality and extracted data. Non-RCTs and non-English articles were excluded. The primary endpoint was mortality and secondary endpoints included adverse events (safety) and treatment efficacy. Main results Of the 1390 studies initially identified, 18 were assessed for eligibility. Of these, 3 studies (n = 464) fulfilled a priori criteria for inclusion; most studied children with moderate dehydration and none were conducted in resource-poor settings. Volumes and rates of fluid replacement varied from 20 to 60 ml/kg given over 1-2 h (fast) versus 2-4 h (slow). There was substantial heterogeneity in methodology between the studies with only one adjudicated to be of high quality. There were no deaths in any study. Safety endpoints only identified oedema (n = 6) and dysnatraemia (n = 2). Pooled analysis showed no significant difference between the rapid and slow intravenous rehydration groups for the proportion of treatment failures (N = 468): pooled RR 1.30 (95% CI: 0.87, 1.93) and the readmission rates (N = 439): pooled RR 1.39 (95% CI: 0.68, 2.85). Conclusions Despite wide implementation of WHO Plan C guideline for severe AGE, we found no clinical evaluation in resource-limited settings, and only limited evaluation of the rate and volume of rehydration in other parts of the world. Recent concerns over aggressive fluid expansion warrants further research to inform guidelines on rates of intravenous rehydration therapy for severe AGE.